Exploring the bidirectional link between erectile dysfunction and 10-year cardiovascular risk in men with diabetes and hypertension - Hai Nguyen Ngoc Dang; Thang Viet Luong; Anh Kiem Pham; The Trung Le; Nhan Duc Le; Hung Minh Nguyen; Tien Anh Hoang; Binh Anh Ho (Scientific Reports)
Abstract Erectile dysfunction (ED) shares common risk factors with cardiovascular (CV) disease, such as a sedentary lifestyle, obesity, and metabolic syndrome. However, the relationship between ED and CV risk in Vietnam remains unknown. To investigate this, we conducted a multi-center observational study, randomly selecting 2,936 men aged 40 to 69 years in Vietnam, with 385 participants included after exclusions. The study evaluated the 10-year CV risk using the Systematic Coronary Risk Evaluation 2-Diabetes (SCORE2-Diabetes) score and assessed ED using the International Index of Erectile Function (IIEF-5) score. Results showed that men with diabetes mellitus and hypertension had significantly lower IIEF-5 scores compared to healthy individuals (18 [15–22] vs. 23 [20–24], p < 0.001). Additionally, the IIEF-5 score proved effective in identifying patients at very high CV risk, with an area under the curve (AUC) of 0.747, a cutoff point of 18.5, sensitivity of 69.6%, and specificity of 69.9%. Furthermore, we found a significant inverse correlation between SCORE2-Diabetes and IIEF-5 (ρ = -0.45 and p < 0.001). These findings establish a significant connection between ED and CV risk in men with diabetes, underscoring the need for integrated screening and management strategies to address both conditions concurrently.